INTERNET RESEARCH ETHICS: NEW CONTEXTS, NEW CHALLENGES – NEW (RE)SOLUTIONS? - Ess, Charles; Seko, Yukari; Tiidenberg, Katrin; Gray, Mary; Granholm, Camilla; Hård af Segerstad, Ylva; Kasperowski, Dick (AoIR Selected Papers of Internet Research, 2015)
Especially the second set of AoIR guidelines for research ethics (Markham and Buchanan 2012) demonstrate that progress can be made in laying out useful approaches for analyzing and resolving at least very many of emerging ethical challenges facing Internet researchers. But of course, new research possibilities, contexts, and approaches continue to issue in sometimes strikingly novel ethical difficulties that may challenge in turn more established frameworks and guidelines. Critical to the ongoing development of Internet Research Ethics (IRE), then, is to bring forward new cases and difficulties that, as in previous cycles of guideline development, will serve as fruitful foci for reflection and deliberation that then contribute to both improving our abilities to respond to such new challenges and, eventually, the articulation of subsequent guidelines. Hence, our roundtable showcases important examples of contemporary research ethics issues – most especially as these are evoked by new research contexts and foci, and, in several instances, new methodological approaches. Our goal is to evoke dialogue and collective reflection on how these issues may be best resolved, and to thereby lift them up as reference points within and constituents of the evolving development of IRE. Following brief presentations from each of our contributors, our two respondents, both long-time and prominent members of the AoIR ethics committee, will offer comments before then opening the roundtable to discussion with the audience.